2007
DOI: 10.1002/mds.21449
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome induced by zonisamide

Abstract: Restless legs syndrome (RLS) is a phenomenon characterized by an intense and irresistible urge to move the legs associated to sensory complaints and motor restlessness. Symptoms usually occur at night and lead to disrupted sleep and daytime

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Among antiepileptic agents (Table 3), [51][52][53][54] 51 The second zonisamide patient was a 50-year-old woman with chronic migraine headache without response to propranolol, topiramate, valproic acid, and magnesium. Zonisamide was initiated and later increased to 100 mg twice daily.…”
Section: Antiepileptic Case Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among antiepileptic agents (Table 3), [51][52][53][54] 51 The second zonisamide patient was a 50-year-old woman with chronic migraine headache without response to propranolol, topiramate, valproic acid, and magnesium. Zonisamide was initiated and later increased to 100 mg twice daily.…”
Section: Antiepileptic Case Reportsmentioning
confidence: 99%
“…Although her headaches improved, zonisamide was suspended, and her RLS symptoms resolved. 52 Bermejo 53 described topiramate-induced RLS in 2 young women with chronic migraines. The patients' physical, neurological, and laboratory exams were normal.…”
Section: Antiepileptic Case Reportsmentioning
confidence: 99%
“…This dual effect may also be the cause of the several cases of restless legs syndrome due to zonisamide described in the literature. 8,9 On the other hand, studies performed on experimental tremor in rats suggest that the antitremor effects may be achieved by a nondopaminergic mechanism. 10 Although the exact mechanisms of action remain unknown, clinical and experimental data suggest that zonisamide may be useful as a therapy for patients with ET or PD and, according to the results obtained in our patients, this drug may play a role in the treatment of "ET-PD syndrome".…”
Section: Zonisamide In Patients With Essential Tremor and Parkinson'smentioning
confidence: 99%
“…However, pregabalin could theoretically induce RLS because it binds potently to the α 2 -δ subunit and modulates calcium influx at nerve terminals, and thereby reduces the release of several neurotransmitters including glutamate, norepinephrine, serotonin, dopamine, and substance P 13-17. Furthermore, there has been a case report of RLS being induced by zonisamide, which is a type of anticonvulsant like pregabalin 18. However, it was reported that pregabalin was effective in the treatment of secondary RLS for patients with neuropathic pain in a recent open trial 19.…”
Section: Discussionmentioning
confidence: 99%